ISCO-Based Analysis of Internship Activities as a Basis for the Development of Sustainable Automotive Vocational Skills - Rasyid Sidik; Ngatou Rohman (Integrated Science Education Journal, 2026)
Purpose of the study: Internship activities can serve as a reference for the skills vocational education institutions require to produce competent graduates. By analyzing internship activities by International Standard Classification of Occupations (ISCO) skill level, the aim is to create a mapping of automotive skills. Methodology: A qualitative approach was employed to analyze 15 internship documents, including activity notes and reports validated by industry experts. The interview participants, selected using purposive sampling, consisted of 5 vocational internship supervisors. The analysis process included data collection, reduction, coding, data triangulation, and interpretation, using NVivo 12. Main Findings: The research results indicate that the foundational competencies in automotive include ISCO 1 skills in terms of work ability and the maturity of soft skills related to the job. The demand for hard skills is driven by jobs equivalent to ISCO skill levels 2; however, higher-level skills, namely ISCO levels 3 and 4, are also required for jobs involving advanced thinking and decision-making in the automotive after-sales industry. Document analysis results reveal the types of skills vocational education institutions can prepare students to engage with, including simulation-based learning, project-based learning, problem-based learning, and work-based learning. Novelty/Originality of this study: Ultimately, this study demonstrates sustainable skill mapping based on job types and ISCO skill levels at low cost through systematic, integrative steps, leveraging the potential of annual industrial internship activities and serving as a reference for other professional competencies.